Aetiopathogenesis of severe cutaneous adverse reactions (SCARs) in children: A 9‐year experience in a tertiary care paediatric hospital setting. Issue 1 (28th October 2019) - Liccioli, Giulia; Mori, Francesca; Parronchi, Paola; Capone, Manuela; Fili, Lucia; Barni, Simona; Sarti, Lucrezia; Giovannini, Mattia; Resti, Massimo; Novembre, Elio M.
Abstract: Background: Severe cutaneous adverse reactions (SCARs) are delayed‐type hypersensitivity reactions to drugs including as follows: Drug Reaction with Eosinophilia and Systemic Symptoms (DRESS), Stevens‐Johnson syndrome (SJS), Toxic Epidermal Necrolysis (TEN) and Acute Generalized Exanthematous Pustulosis (AGEP). Incidence, triggers and management of SCARs have not been investigated in large‐scale epidemiological studies on children. Objective: The aim of our study was to collect epidemiological, clinical and aetiological data from children with SCARs referred to our tertiary care paediatric hospital of Florence. Methods: From 2010 to 2018 charts of children with diagnosis of SCAR were reviewed, and data collected during the acute phase and/or the subsequent allergy evaluation. Patients underwent patch tests, intradermal tests and lymphocyte transformation tests. All children were investigated for infectious diseases. Results: Incidence of SCARs in hospitalized children was 0.32% over a 9‐year period. Fifty‐four children were enrolled (31 M; 23 F; median age 6.5 years): 17 cases of DRESS, 30 SJS, 3 TEN, 2 AGEP, 1 linear immunoglobulin A bullous disease (LABD) and 1 pemphigus. Twenty‐eight out of 54 patients underwent drug allergy investigations, and 50% of them resulted positive. Combining clinical history and results of allergy work‐up, 74% SCARs seem to be caused by drugs, 18.6% by both drugs and infections, 3.7% by infections, and 3.7% remained idiopathic. No deaths occurred. Conclusions: In this study, SCARs incidence is in line with literature data. Drugs were most commonly the leading cause. Management of SCARs requires cooperation among professional figures for an early diagnosis and a prompt treatment. Mortality rate seems to be lower in children.